1999
DOI: 10.1046/j.1365-2664.1999.00392.x
|View full text |Cite
|
Sign up to set email alerts
|

Densities of mammals in partially protected areas: the Katavi ecosystem of western Tanzania

Abstract: Summary 0[ In Africa the majority of conservation areas sanction some sort of human activities within their borders but few of them are part of community!based conservation schemes[ The e}ectiveness of these state!owned\ partially protected areas in conserving mammalian fauna is largely unknown[ 1[ Large and medium!sized mammal densities in three di}erent sorts of partially protected area were compared to mammal densities in an adjacent national park in western Tanzania by driving 1842 km of strip transects ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
99
3
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(108 citation statements)
references
References 26 publications
5
99
3
1
Order By: Relevance
“…When compared with private and community regimes, the state was reported as performing better in 9 studies [35,37,38], while private and community regimes were reported as outperforming the state in 12 studies [35,37,[39][40][41][42]. Four studies compared state performance with another state regime [43]. Here state-controlled national park and game controlled area were reported as performing better than forest reserve and open access regimes.…”
Section: Results From Forest Resource Systemsmentioning
confidence: 99%
“…When compared with private and community regimes, the state was reported as performing better in 9 studies [35,37,38], while private and community regimes were reported as outperforming the state in 12 studies [35,37,[39][40][41][42]. Four studies compared state performance with another state regime [43]. Here state-controlled national park and game controlled area were reported as performing better than forest reserve and open access regimes.…”
Section: Results From Forest Resource Systemsmentioning
confidence: 99%
“…Finally, ethnicity is strongly associated with bushmeat consumption in parts of Rio Muni [23]. To refine our understanding of household correlates of bushmeat consumption in western Tanzania where bushmeat activities are prevalent [7,10] we chose the Katavi-Rukwa ecosystem where declines in mammal populations are in evidence [24][25][26][27]. We focused on Mpimbwe Division in particular, a rapidly growing area occupied by several ethnic groups and for which there is solid ethnographic background [28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…Although protected areas are recognised as a key element in conservation, studies show that partially protected areas (IUCN category B IV) do not protect biodiversity as well as strictly protected areas (Caro et al 1998;Caro 1999;Pelkey et al 2000;Setsaas et al 2007). Nevertheless, partially protected areas compose a significant part of the protected area network in Southern Africa (WRI 2005).…”
Section: Introductionmentioning
confidence: 99%